The precursors of CD8 + tissue resident memory T cells: from lymphoid organs to infected tissues - Kok, Lianne; Masopust, David; Schumacher, Ton N (Nature reviews. Immunology, 2022)
CD8 tissue resident memory T cells (T cells) are essential for immune defence against pathogens and malignancies, and the molecular processes that lead to T cell formation are therefore of substantial biomedical interest. Prior work has demonstrated that signals present in the inflamed tissue micro-environment can promote the differentiation of memory precursor cells into mature T cells, and it was therefore long assumed that T cell formation adheres to a 'local divergence' model, in which T cell lineage decisions are exclusively made within the tissue. However, a growing body of work provides evidence for a 'systemic divergence' model, in which circulating T cells already become preconditioned to preferentially give rise to the T cell lineage, resulting in the generation of a pool of T cell-poised T cells within the lymphoid compartment. Here, we review the emerging evidence that supports the existence of such a population of circulating T cell progenitors, discuss current insights into their formation and highlight open questions in the field.